Investigation of long non-coding RNAs in extracellular vesicles from low-volume blood serum specimens of colorectal cancer patients - Boudna, Marie; Machackova, Tana; Vychytilova-Faltejskova, Petra; Trachtova, Karolina; Bartosova, Renata; Catela Ivkovic, Tina; Al Tukmachi, Dagmar; Jugas, Robin; Pifkova, Lucie; Orlickova, Jana; Kotoucek, Jan; Pavlikova, Marketa; et al. (Clinical and experimental medicine, 2024)
Colorectal cancer (CRC) is the second most prevalent cancer type worldwide, which highlights the urgent need for non-invasive biomarkers for its early detection and improved prognosis. We aimed to investigate the patterns of long non-coding RNAs (lncRNAs) in small extracellular vesicles (sEVs) collected from low-volume blood serum specimens of CRC patients, focusing on their potential as diagnostic biomarkers. Our research comprised two phases: an initial exploratory phase involving RNA sequencing of sEVs from 76 CRC patients and 29 healthy controls, and a subsequent validation phase with a larger cohort of 159 CRC patients and 138 healthy controls. Techniques such as dynamic light scattering, transmission electron microscopy, and Western blotting were utilized for sEV characterization. Optimized protocol for sEV purification, RNA isolation and preamplification was applied to successfully sequence the RNA content of sEVs and validate the results by RT-qPCR. We successfully isolated sEVs from blood serum and prepared sequencing libraries from a low amount of RNA. High-throughput sequencing identified differential levels of 460 transcripts between CRC patients and healthy controls, including mRNAs, lncRNAs, and pseudogenes, with approximately 20% being lncRNAs, highlighting several tumor-specific lncRNAs that have not been associated with CRC development and progression. The validation phase confirmed the upregulation of three lncRNAs (NALT1, AL096828, and LINC01637) in blood serum of CRC patients. This study not only identified lncRNA profiles in a population of sEVs from low-volume blood serum specimens of CRC patients but also highlights the value of innovative techniques in biomolecular research, particularly for the detection and analysis of low-abundance biomolecules in clinical samples. The identification of specific lncRNAs associated with CRC provides a foundation for future research into their functional roles in cancer development and potential clinical applications.
Keywords: RNA dlouhá nekódující; Biomarker; extracelulární vezikuly; Serum; Extracellular Vesicles; sekundární malignity; lncRNAs; Humans; biologické markery; Neoplasms, Second Primary; kolorektální nádory; lidé; Biomarkers; Colorectal cancer; EVs; sérum; Colorectal Neoplasms; RNA, Long Noncoding